Functional Roles of Non-coding RNAs in the Interaction Between Host and Influenza A Virus - Sajjad, Nelam; Wang, Song; Liu, Ping; Chen, Ji-Long; Chi, Xiaojuan; Liu, Shasha; Ma, Shujie (Frontiers in Microbiology, 2021)
Non-coding RNAs (ncRNAs) are extensively expressed in various cells and tissues, and studies have shown that ncRNAs play significant roles in cellular regulations. Over the past few decades, however, the knowledge about ncRNAs has been increased dramatically, due to their transcriptional ability and multiple regulatory functions. Typically, ncRNAs include housekeeping ncRNAs and regulatory ncRNAs (e.g., miRNAs, piRNAs, Y RNAs, vault RNAs, lncRNAs, and circRNA). Previous studies have revealed that various ncRNAs are significantly involved in the host responses to virus infection and play critical roles in the regulation of host-virus interactions. In this review, we discuss the conceptual framework and biological regulations of ncRNAs to elucidate their functions in response to viral infection, especially influenza A virus infection. In addition, we summarize the ncRNAs that are associated with innate immunity and involvement of interferons and their stimulation genes (ISGs) during the influenza A virus infection.